New product development in textiles innovation and production - Horne, L. (Woodhead Pub., 2012)
Annotation An increasingly important feature for the technical textile industry is to produce textiles faster and to achieve more effective new product development. This book will not only provide a fascinating overview of how products are launched, but will also be a source of practical guidance for developing textile products successfully. The collection begins with some background information that introduces the reader to the principles of innovation. The remainder of the book provides a collection of international case studies from across the textile industry. Chapters will describe actual new product development projects, identifying the problems that were faced and lessons that can be learnt. Topics range from technical textiles to end uses of textiles, such as the automotive and packaging industries.
Keywords: Textile industry -- Technological innovations.; New products.; Product management.; Textile fabrics -- Technological innovations.; elektronické knihy; electronic books